Debating points: marriage and family issues - Tischler, Henry ed. (New Jersey: The Prntice Hall, Inc, 2001)
Contents: Is the american family in trouble,the famiy values debate,the american family and the nostalgia trap,has fatherhooh been devalued,is the widespread use of day care harming our children,is today is high divorce rate a problem for society,should limits be placed on the use of reproductive technoloy,have we exaggerated the extent of domestic violence.
Includes bibliographical references and index
Keywords: Family - United States